Identification and analysis of resilience strategies for the retail sector in the face of supply chain disruptions abstract - Peña Tipian, Gonzalo Alfredo (2024)
Faced with the growing problem of disruptions affecting the supply chains of companies around the world, this article seeks to provide a theorical contribution based on the compilation of resilience strategies and the concepts they entail. A thorough literature review, classification of the relevant concepts found, and validation and discussion by experts in a sector that has not been previously covered, which is retail in Peru, were carried out. The main resilience strategies in different global supply chains that could be applied on the retail sector were identified, grouping them into 16 proposed macro strategies, facing 8 major disruptions and applicable in 3 phases of resilience (preparedness, response and recovery). The results are expected to serve as a guide for small, medium or large companies in the face of future local or global events that may affect their supply chain.